PCK1 is negatively regulated by bta‐miR‐26a, and a single‐nucleotide polymorphism in the 3′ untranslated region is involved in semen quality and longevity of Holstein bulls. Issue 3 (1st February 2016) - Huang, Jinming; Guo, Fang; Zhang, Zebin; Zhang, Yuanpei; Wang, Xiuge; Ju, Zhihua; Yang, Chunhong; Wang, Changfa; Hou, Minghai; Zhong, Jifeng
SUMMARY: Phosphoenolpyruvate carboxykinase 1 (PCK1) is a multi‐functional enzyme that plays important roles in physiological processes, including reproduction. We previously reported that the PCK1 transcript has five splice variants; PCK1‐AS4, which lacks exon 5, is enriched in the testis of Holstein bulls. In the present study, we profiled select PCK1 transcript variants in the testis, epididymus, and semen of high‐ and low‐performance bulls, and examined the possibility that microRNAs may be involved in single nucleotide polymorphism (SNP)‐mediated modulation of PCK1 expression. PCK1‐AS4 abundance is not significantly different between high‐ and low‐performance bulls. Luciferase reporter assays, however, showed that bovine PCK1 expression is repressed by bta‐miR‐26a in HepG2 hepatocyte cells. One SNP (c. + 2183 G > T) at the miRNA‐binding site of PCK1 does not influence PCK1 expression, but is associated with elevated ejaculation volume, fresh sperm motility, and genomic estimated breeding value of longevity, as well as with reduced values of composite index and calving ease. Collectively, the identified 3′‐untranslated‐region SNP variant highlights the importance of PCK1 in the fecundity of Holstein bulls, and implicates a role for bta‐miR‐26a in regulating PCK1 abundance. Further study is needed to assess the effects of other genetic variants in 5′‐flanking region and exons of PCK1 on enzyme levels in the testis and sperm. Mol. Reprod. Dev. 83: 217–225, 2016. © 2016 Wiley Periodicals, Inc .